Teeth Tales: a community-based child oral health promotion trial with migrant families in Australia. Issue 6 (11th June 2015) - Gibbs, Lisa; Waters, Elizabeth; Christian, Bradley; Gold, Lisa; Young, Dana; de Silva, Andrea; Calache, Hanny; Gussy, Mark; Watt, Richard; Riggs, Elisha; Tadic, Maryanne; Hall, Martin; et al.
Abstract : Objectives: The Teeth Tales trial aimed to establish a model for child oral health promotion for culturally diverse communities in Australia. Design: An exploratory trial implementing a community-based child oral health promotion intervention for Australian families from migrant backgrounds. Mixed method, longitudinal evaluation. Setting: The intervention was based in Moreland, a culturally diverse locality in Melbourne, Australia. Participants: Families with 1–4-year-old children, self-identified as being from Iraqi, Lebanese or Pakistani backgrounds residing in Melbourne. Participants residing close to the intervention site were allocated to intervention. Intervention: The intervention was conducted over 5 months and comprised community oral health education sessions led by peer educators and follow-up health messages. Outcome measures: This paper reports on the intervention impacts, process evaluation and descriptive analysis of health, knowledge and behavioural changes 18 months after baseline data collection. Results: Significant differences in the Debris Index (OR=0.44 (0.22 to 0.88)) and the Modified Gingival Index (OR=0.34 (0.19 to 0.61)) indicated increased tooth brushing and/or improved toothbrushing technique in the intervention group. An increased proportion of intervention parents, compared to those in the comparison group reported that they had been shown how to brush their child's teeth (OR=2.65 (1.49 to 4.69)). Process evaluation results highlighted the problems with recruitment and retention of the study sample (275 complete case families). The child dental screening encouraged involvement in the study, as did linking attendance with other community/cultural activities. Conclusions: The Teeth Tales intervention was promising in terms of improving oral hygiene and parent knowledge of tooth brushing technique. Adaptations to delivery of the intervention are required to increase uptake and likely impact. A future cluster randomised controlled trial would provide strongest evidence of effectiveness if appropriate to the community, cultural and economic context. Trial registration number: Australian New Zealand Clinical Trials Registry (ACTRN12611000532909).